The Use of Creative Board Media in Improving Arabic Writing Skills - Syafei, Isop; Syukriya, Aini Ummu (Universitas Islam Negeri Raden Intan Lampung, 2020)
The learning process of writing Arabic occasionally finds difficulties in examining the validity of writing or answers from the students as soon as possible evenly in the classroom, because of limited time. The teacher is required to be able to manage learning as well as possible, so that the interaction between students and teacher in the process of teaching activities runs optimally and comprehensively to all students in the class. This research aims to determine the efforts of the Arabic language teacher at Islamic senior high school of P.B. Soedirman 1 Bekasi in the use of creative board media to improve the Arabic writing skills of the students. The method used in this research is experimental method. The subject of research are students of class X KBC (Kelompok Belajar Cepat - Fast Learning Group) majoring in social studies (16 students), and students of class X majoring in science (22 students). Data collection technique used in this assignment project is documentation. In analyzing data, the researcher uses deductive analysis techniques. The results showed that; 1) the Arabic teacher has sought to use effective and efficient media in the learning process, 2) students can also get benefit from the Creative Board media to be more enthusiastic in practicing Arabic writing. The crative board media is hence very feasible to be implemented in the process of learning a foreign language.